PROJECT MANAGEMENT AT THE LEVEL OF REGIONS (Development Service Industry Management, 2024)
Research on the management of the projects at the regional level. Diverse methods and approaches were employed in the process of completing the stated objectives of the presented paper. For instance, the abstract and logical method was used to clearly define the goals and objectives of the study.  The analytical and monographic approach was implemented to analyze literary sources, legislative and regulatory acts related to the operation of projects. Stability in prose transactions, such as financial, social and environmental sustainability, is one of the most prominent issues of modern times. Increased attention to sustainable business operations changed the view of researchers and the corporate community to the management of projects. Today, the resilience in business operations, as well as the stability of natural and environmental resources, is of paramount importance, which has further caused a huge impact on the formation, planning, and the performance of project management activities. This study also defines and discusses future opportunities to apply computing procedures to evaluate and optimize the issues of stability in the management of projects, such as stability in projects, and then obtaining optimized solutions for a formulated problem to achieve stability in projects. In order to achieve stability to the projects, the feedback component must be added at each level of organization of project management, and feedback can be taken for each decision, actions and processes, and, in addition, reviews should be evaluated and viewed by an arbitration organization interested parties and clients to implement corrective measures to achieve stability in projects. A new integrated frame is also determined and presented with the inclusion of feedback function to evaluate each solution and actions taken to the stability of the projects. The recommendations provided in the article can be applied to the creation of conditions for sustainable development of Ukraine.
Keywords: management of the project; stability; system; region; food complex